Ideas, Interests, and Construction of a Northeast Asian Community - Park, Hun Joo (Journal of East Asian Affairs, 2004)
This paper investigates the root causes of the seemingly forever-troubled efforts to construct an economic community in the Northeast Asian region. As of 2000, for instance, the three Northeast Asian countries of Japan, China, and Korea accounted for 22 percent of the world's GDP, which represented about 75 percent of the EU's GDP or 79 percent of NAFTA's GDP. In the same year, however, the intra-bloc trade ratio stayed at only 20 percent of the total for the Northeast Asian region, while the equivalent figures for the EU and NAFTA recorded 60 percent and 47 percent, respectively. More ominously, of the comparatively meager amount of cooperation in the economic arena, even less spilled over into the security realm. This paper argues that a principled state action and an international communitarian approach to resolving the security dilemma on the part of the concerned countries are at least as important as power and interest-centric approaches and, in fact, are critical and indispensable to crafting an economic and security community in the region, and the world.